Detection of highly resistant Enterobacteriaceae (HRE) from hospital isolates within Bauchi metropolis (Journal of Pure and Applied Sciences (Science Forum), 2026)
The Enterobacteriaceae are Gram-negative, facultative anaerobes that fermenting sugars to produce lactic acid. Most prevalent among this family are Escherichia coli and Klebsiella pneumonia, recently these species developed resistance to many antibiotics with few exceptions among which include Beta lactams antibiotics. This study explores the susceptibility profile of Enterobacteriaceae to commonly prescribed antibiotics.  A total of 485 Enterobacteriaceae isolate mostly Klebsiella pneumoniae E. coli, Proteus species, Enterobacter species, Salmonella typhi, and Shigella species) from Urine, High Virginal Swab, Endocervical Swab, Sputum, and Blood were collected from the selected hospital within Bauchi metropolis from April to August 2016 to study the Resistant pattern of Enterobacteriaceae (HRE) and some extended spectrum β-lactamases (ESBL) producing K. pneumoniae among clinical isolates in the hospital setting. Isolates were tested for possible ESBL production and were phenotypically confirmed. The Kirby Bauer disk diffusion method was followed base on Clinical and Laboratory Standard Institute guidelines, Antibiotic susceptibility testing was further conducted. Among the 485 isolate isolates processed, 347 (71.5%) were tested for multidrug resistant while 138 (28.5%) Klebsiella pneumoniea were tested for ESBL production. 56 (40.6%) of K. pneumoniae are ESBL producers while 82 (59.4%) are non ESBL Producers. The phenotypic assay confirms the presence of extended drug-resistant K. pneumoniae with some Enterobacteriaceae. There is also a need for further research to identify the effect of infection with ESBL producing bacteria within the study area.